Synaptic connectivity of the TRPV1-positive trigeminal afferents in the rat lateral parabrachial nucleus - An, Su Bin; Cho, Yi Sul; Park, Sook Kyung; Kim, Yun Sook; Bae, Yong Chul (Frontiers in Cellular Neuroscience, 2023)
Recent studies have shown a direct projection of nociceptive trigeminal afferents into the lateral parabrachial nucleus (LPBN). Information about the synaptic connectivity of these afferents may help understand how orofacial nociception is processed in the LPBN, which is known to be involved primarily in the affective aspect of pain. To address this issue, we investigated the synapses of the transient receptor potential vanilloid 1-positive (TRPV1+) trigeminal afferent terminals in the LPBN by immunostaining and serial section electron microscopy. TRPV1+ afferents arising from the ascending trigeminal tract issued axons and terminals (boutons) in the LPBN. TRPV1+ boutons formed synapses of asymmetric type with dendritic shafts and spines. Almost all (98.3%) TRPV1+ boutons formed synapses with one (82.6%) or two postsynaptic dendrites, suggesting that, at a single bouton level, the orofacial nociceptive information is predominantly transmitted to a single postsynaptic neuron with a small degree of synaptic divergence. A small fraction (14.9%) of the TRPV1+ boutons formed synapses with dendritic spines. None of the TRPV1+ boutons were involved in axoaxonic synapses. Conversely, in the trigeminal caudal nucleus (Vc), TRPV1+ boutons often formed synapses with multiple postsynaptic dendrites and were involved in axoaxonic synapses. Number of dendritic spine and total number of postsynaptic dendrites per TRPV1+ bouton were significantly fewer in the LPBN than Vc. Thus, the synaptic connectivity of the TRPV1+ boutons in the LPBN differed significantly from that in the Vc, suggesting that the TRPV1-mediated orofacial nociception is relayed to the LPBN in a distinctively different manner than in the Vc.